Evaluation of the STOK Bina Guna Football Student Activity Unit (UKM) Development Program - Eka Abdurrahman; Brema Bangun; Meria Zega; Muhammad Adib Pidanto; Mhd. Alvin Syahri, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. The purpose of this study was to evaluate the coaching program of the STOK Bina Guna Football Student Activity Unit. The STOK Bina Guna Football Student Activity Unit is one of the organizations that organizes the football coaching process in Samarinda. The coaching process is determined, among other things, by training programs developed by coaches. Other factors that also determine achievement are organizational elements, aspects of coaches, athletes, supporting facilities and infrastructure, supporting funding, and also participation and support from the community and government. The declining performance of the STOK Bina Guna Football Student Activity Unit became the basis for the researcher to conduct this research.Materials and Methods. The research method used was descriptive qualitative. The approach used in this study was the CIPP model. Data collection techniques included observation, interviews, and documentation with administrators, coaches, athletes, and parents.Results. The research results concluded: 1) Context was concluded with a good category. 2) Input regarding the aspect of human resource availability was concluded with a good category. For the aspect of the availability of facilities and infrastructure was concluded with a good category and funding sources were concluded with a good category. 3) Process regarding the aspect of training program implementation, athlete recruitment system and coordination was concluded with a good category while the aspect of the coach recruitment system and the use of facilities and infrastructure was concluded with a moderate category. 4) Product regarding the aspect of achievement and welfare was concluded with a moderate category.Conclusions. The coaching program carried out by the STOK Bina Guna Football UKM has not been implemented well, from several aspects that are used as indicators for evaluating the coaching program, it is in the moderate and less than adequate categories.